The Effect of Coffee Consumption on Individuals with Acute Stress Disorder - Masayu Nandhia Dwiputri; Ramadhani, Aji Fajar (Journal of Coffee and Sustainability, 2024)
Caffeine, or the consumption of coffee with antioxidant content, has many benefits, one of which is reducing symptom stress in individuals. Research purposes This is to know the influence of consuming coffee against declining symptoms of stress in individuals with Stress Acute Disorder who experienced​ traumatic incidents. Research methods This quantitative approach experiment uses one group pre-test - post-test design. Pre-test and post-test will be measured using the Acute Stress Disorder Scale (ASDS) in individuals diagnosed with the Stress Acute Disorder. There are eight types of acute sex: men and women aged 20-25 years. Treatment is done by giving the subjects two glasses of coffee daily with a dose of 10 mg or equivalent with 25-35 ml of liquid espresso. The paired sample t-test showed results that the mean for the average result is 32,750 marks. This is the difference between the average values pre-test and post-test with a Sig of 0.000 (p < 0.50). The results of the paired sample t-test are known as t value = 55,499. This matter is worth positive because the average pre-test score is taller than the mean post-test score, meaning fewer stress symptoms exist in individuals with Stress Acute Disorder.